Pengaruh Korean Wave dan Brand Ambassador pada Pengambilan Keputusan Konsumen - Amarilis Rahmadani; Yunita Anggarini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study aims to analyze the influence of the Korean wave and brand ambassadors on consumer purchasing decisions. This research is a quantitative study using a population of consumers of Nacific cosmetic products from South Korea. By using purposive sampling technique, a sample of 100 respondents was tested in this study. The analytical method used is binary logistic regression analysis. The results showed that the decision to purchase Korean cosmetic products was strongly influenced by the Korean wave, and vice versa was not influenced by the brand ambassador. This study shows that Korean culture has a fairly strong influence on Indonesian consumers' decisions to buy cosmetic products. Meanwhile, Korean influencers have no influence on purchasing decisions, which factors need to be studied. This study adds a reference to behavioral research related to the effects of cultural change in Indonesia, especially the influence of Korean culture.